Change in body composition of premature infants from parenteral nutrition discontinuation to term equivalent age. (December 2020) - Paviotti, Giulia; De Cunto, Angela; Travan, Laura; Bua, Jenny; Miron, Tatiana; Cont, Gabriele; Demarini, Sergio
Abstract: Aim: To compare body composition (BC) of premature infants at parenteral nutrition (PN) suspension and at term equivalent age (TEA). Methods: Body weight, fat mass (FM), fat free mass (FFM) and FM as % of body weight were measured in infants born at <32 gestational weeks by air-displacement plethysmography at PN suspension and at TEA in a tertiary level hospital. Z-scores were calculated for BC and anthropometric measurements. Nutritional and clinical data were obtained during hospital stay. BC, weight and length were measured at birth in a sample of infants born at term for comparison. Results: Thirty premature infants with birth weight of 1198 ± 270 g and gestational age of 29.8 ± 1.8 weeks were included. At PN suspension, at 32.6 ± 1.6 postconceptional weeks, FFM z-score was similar to FFM z-score measured at TEA, at 39.8 ± 0.7 postconceptional weeks (−1.43 ± 1.27 vs −1.78 ± 1.64, p  = 0.26), while FM z-score and %FM z-score at PN suspension were lower than those measured at TEA (FM z-score: 0.23 ± 0.62 versus 2.04 ± 1.00, p  < 0.0001 and %FM z-score: 0.66 ± 0.76 versus 2.08 ± 1.07, p  < 0.0001). At TEA, weight and length of premature infants were similar to those of term-born infants (3130 ± 340 g vs 3350 ± 340 g; 49.2 ± 2.4 cm vs 50.2 ± 2.5 cm, respectively), but %FM was higher (21.3 ± 4.2% vs 9.2 ± 4.4%, p  < 0.001); higher exclusive enteral caloric and protein intakes were associated with a decrease in FM z-scores from PN suspension to TEA. Conclusion: In our sample of premature infants, fat free mass z-score was similar, while fat mass and % fat mass z-scores increased substantially from parenteral nutrition suspension to term-equivalent age. Nutritional intakes during exclusive enteral nutrition did not seem to contribute to such increase. Highlights: Nutrition in preterm infants is challenging. In preemies fat-free mass was unchanged and fat mass increased from parenteral nutrition suspension to term equivalent age. Anthropometrics were similar, adiposity was higher in preemies than in term born infants at similar postconceptional age. Enteral macronutrient intakes did not seem to contribute to fat mass accumulation during exclusive enteral nutrition.